2022
DOI: 10.1002/hsr2.669
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive decline as a major predictor of nonadherence to antiretroviral therapy among adults living with HIV in Dodoma region, central Tanzania

Abstract: Background The survival of people living with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome largely depends on good adherence to antiretroviral medications. Neuropsychiatric conditions such as major depressive disorders (MDDs) and neurocognitive disorders, in particular, are common in the HIV population and attributed to suboptimal adherence to antiretroviral treatment and overall poor clinical outcomes. This study aimed to determine the association between neurocognitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Our study showed that suboptimal adherence was significantly associated with neurocognitive impairment. Other studies have also shown that neurocognitive impairment is a major predictor of poor adherence to ART [ 74 ]. However, the temporal relationship between poor adherence and poor cognitive functioning is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that suboptimal adherence was significantly associated with neurocognitive impairment. Other studies have also shown that neurocognitive impairment is a major predictor of poor adherence to ART [ 74 ]. However, the temporal relationship between poor adherence and poor cognitive functioning is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive impairment, which is frequently comorbid with depression and problematic substance use, may also play a role in ART non-adherence ( Nyundo, 2022 ; Rubin and Maki, 2019 ; Thaler et al, 2015 ). Along these lines, one study reported that PLWH with HIV-associated neurocognitive disorder had lower resting state functional connectivity in the CEN compared to healthy control participants ( Chaganti et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these few studies, findings are equivocal and methods may be suboptimal. For instance, whereas a study conducted in Malawi found no relationship between cognitive impairment and adherence [ 25 ], another one conducted in Tanzania [ 26 ] found that impaired cognitive performance was a strong predictor of suboptimal adherence. However, this latter study used only the Montreal Cognitive Assessment (MoCA), a screening tool, to measure cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigating the association between cognitive performance and adherence have used either self-report or MEMS [ 16 , 17 , 19 , 22 , 24 , 26 ]. Of the studies reviewed above, one study measured adherence using pharmacy refill record [ 18 ] and another used plasma ART concentrations [ 25 ].…”
Section: Introductionmentioning
confidence: 99%